Experimental Study on Heat Transfer Characteristics on Intersecting Spiral Finned Tube Type on Heat Exchanger - Syahril, Muhammad; Syuhada, A.; Hamdani, Hamdani (Politeknik Negeri Lhokseumawe, 2024)
Compact heat exchangers play an important role in the industrial world, one of their applications being in thermal machines to dissipate heat generated during mechanical processes. To improve the performance of heat exchangers, many studies have been conducted, including the addition of spiral fins, and the spacing of these fins on the outer surface. This study examines the heat transfer characteristics of the outer surface. The heat exchanger is made of galvanized pipe with an inner diameter of 20 mm and an outer diameter of 22 mm. It has a passage length of 300 mm with a sharp turn of 81 mm. The spiral fins are made of aluminum, with a thickness of 0.3 mm, a spiral fin height of 10 mm, and a distance of 30 mm between the spiral fins. The cross-section of the spiral fins varies, including options without spiral fins, without spiral fins, without intersecting spiral fins, with intersecting 2 mm spiral fins, intersecting 5mm spiral fins, and intersecting 7mm spiral fins. Heat exchangers are supplied with hot at a constant inlet temperature of 80C and a flow rate of 0.57 kg/s. The fan operates at speeds of 3.59 m/s, 4.45 m/s and 5.07 m/s. The results show that the highest heat transfer rate and heat transfer coefficient are produced by the heat exchanger with a cross-section of 5 mm intersecting spiral fins, specifically 11,682.7 W and 604 W/m2.K.